2012
DOI: 10.1007/s00395-012-0258-4
|View full text |Cite
|
Sign up to set email alerts
|

“Conditional Conditioning” in cardiac bypass surgery

Abstract: Coronary artery bypass graft (CABG) surgery remains the procedure of choice for coronary artery revascularization in patients with multi-vessel coronary artery disease (CAD). For patients undergoing elective isolated CABG surgery, clinical outcomes are very good (1.5 % in-hospital mortality in the UK) [35]. However, increasing numbers of higher risk patients are being operated, resulting in higher in-hospital mortality rates. The reasons for this increase in high risk patients include: patients being older (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…For example, some studies enrolled only stable patients undergoing CABG, whereas others included valve surgeries, patients with unstable coronary disease, and high-risk patients (ie, double and triple valve surgeries, mitral valve surgery, and combined CABG and valve surgery). 16,98,[123][124][125] Attempting to draw conclusions from mixed populations is problematic, as it assumes that the effects of remote conditioning will be comparable among all cohorts-an assumption that has not been tested and may be flawed. Additional sources of variation among studies include the choice of anesthetic and cardioplegic agents, the inclusion versus exclusion of patients with diabetes mellitus, and the temporal aspects of the remote conditioning algorithm.…”
Section: Future Of Remote Conditioning: Establishing the Determinantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some studies enrolled only stable patients undergoing CABG, whereas others included valve surgeries, patients with unstable coronary disease, and high-risk patients (ie, double and triple valve surgeries, mitral valve surgery, and combined CABG and valve surgery). 16,98,[123][124][125] Attempting to draw conclusions from mixed populations is problematic, as it assumes that the effects of remote conditioning will be comparable among all cohorts-an assumption that has not been tested and may be flawed. Additional sources of variation among studies include the choice of anesthetic and cardioplegic agents, the inclusion versus exclusion of patients with diabetes mellitus, and the temporal aspects of the remote conditioning algorithm.…”
Section: Future Of Remote Conditioning: Establishing the Determinantsmentioning
confidence: 99%
“…Additional sources of variation among studies include the choice of anesthetic and cardioplegic agents, the inclusion versus exclusion of patients with diabetes mellitus, and the temporal aspects of the remote conditioning algorithm. Among these, the 2 most important confounders might potentially be the anesthetic regimen (in particular, the use of propofol), 123,126 together with variability in the time at which the remote stimulus was applied (after induction of anesthesia but before the first surgical incision versus after the first incision but before cardiopulmonary bypass). 120,121,[123][124][125] However, this raises the second issue: we have limited insight into the consequences of this variability.…”
Section: Future Of Remote Conditioning: Establishing the Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of systematic characterization may come at a price: that is, in contrast to the first, largely positive outcomes (reviewed in 22,23,25 ), studies reporting no clinical benefit of RIPC are emerging. [66][67][68] These discrepancies may reflect variations among the RIPC algorithms that have been applied (use of arms versus legs, in one limb or two: summarized in 23,69 ), the interval between the remote stimulus and the onset of myocardial ischemia and, perhaps most importantly, differences in baseline patient characteristics, specific surgical procedures and choice of anesthetic agents. [69][70][71] Resolution of these issues -and the resultant progression from 'hypotheses non fingo' to a greater conceptual understanding of RIPC -will be critical to the future of remote ischemic conditioning.…”
Section: Resultsmentioning
confidence: 98%
“…[51][52][53][54][55][56][57][58][59][60][61][62] Not all studies using a remote preconditioning protocol reported cardioprotection, [63][64][65][66] and the potential reasons underlying these discrepant results are still under discussion, but possibly relate to anesthesia 67 or to the timing of the remote protocol with respect to skin incision. 68 Kottenberg et al 61 found cardioprotection by remote preconditioning only under isoflurane, but not under propofol anesthesia; in contrast, isoflurane was reported to induce cardioprotection per se and thus obviate protection by remote preconditioning. 65 Apart from the issue of anesthesia, the small number of patients in all studies on remote preconditioning with surgical revascularization so far makes them very susceptible for a type II error.…”
mentioning
confidence: 97%